The low-temperature thermo-tectonic evolution of the western Tian Shan, Uzbekistan - Jepson, G.; Glorie, S.; Konopelko, D.; Mirkamalov, R.; Danišík, Martin; Collins, A. (Elsevier BV, 2018)
The Kyzylkum-Nurata region represents a key area in understanding the tectonic evolution of the western Tian Shan. In this study, we present new thermochronological data (apatite fission track and apatite (U-Th-Sm)/He) and associated thermal history models for 45 igneous samples from the Kyzylkum-Nurata Segment of South Tian Shan on the territory of Uzbekistan and Tajikistan. Our data show that the Kyzylkum-Nurata Segment experienced a multi-phase Mesozoic thermal history that differs from previously studied segments of the Tian Shan. A Triassic (~220–200 Ma) cooling signal is widespread throughout the Tian Shan and is interpreted as being associated with exhumation following the closure of the Palaeo-Asian Ocean. Following this period of fast cooling, the Kyzylkum-Nurata Segment experienced a period of slow cooling and erosion in the Early Jurassic (~190–160 Ma). However, in contrast to other parts of the Tian Shan, our study area preserves evidence for rapid cooling during the Late Jurassic–Early Cretaceous (~160–120). Given that this rapid cooling signal was only recorded for samples in association with major structures (e.g., relic suture-shear zones), we interpret this event as a period of fault reactivation related with tectonic processes at the Eurasian margin of the Tethys Ocean. Subsequently, the Late Cretaceous–early Palaeogene (~100–50 Ma) is characterised by slow cooling and erosion. Since the late Palaeogene, the basement of the Tian Shan experienced cooling related to the India-Eurasia collision. The thermal signal of this collision has been extensively recorded in the high-altitude Kyrgyz Tian Shan. Within the low-relief Kyzylkum-Nurata Segment, this Cenozoic overprint is not recorded, allowing for a detailed assessment of the Mesozoic thermal and landscape evolution of the western Tian Shan. Our study demonstrates that the Cretaceous Uzbek Tian Shan was characterised by a series of parallel, linear mountain belts that formed along suture zones during fault reactivation.